(untitled) (International Journal of Engineering and Computer Science, 2018)
IEEE 802.15.4 (Zigbee) is a leading technology for wireless sensor network, it is a medium access control and physical layer standard specially designed for short range wireless communication. Zigbee is used in applications that require low rate, secure networking, low complexity and power saving consumption. Generally Zigbee is typically used for environmental monitoring applications such as remote control monitoring system, health care device, home automation, electrical meter with in home displays, traffic management system etc. Routing protocol in zigbee has been classified on the basis of their route deterministic protocols such as ZRP, AODV and these protocols are designed considering inherent capacity constraint i.e. power, memory, bandwidth etc. In Zigbee Network On increasing the traffic load. The ratio of successfully data delivery is reduced, by which we not get efficient performance and throughput. For enhancing the performance and throughput of Zigbee different researcher has proposed different algorithm and methods which are summaries below in this paper.